2018
DOI: 10.1016/j.diabres.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake by food group of individuals with type 2 diabetes mellitus: A systematic review

Abstract: Individuals with T2DM do not comply with food group recommendations; particularly for fruit, vegetables, dairy and grains. Longitudinal research is required to better understand how food group intake changes over time after diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 42 publications
1
20
0
5
Order By: Relevance
“…All reported cross-sectional data. The majority of participants, with type 2 diabetes, were consuming less than the recommended amount of fruit and vegetables [30].…”
Section: Homa-irmentioning
confidence: 99%
“…All reported cross-sectional data. The majority of participants, with type 2 diabetes, were consuming less than the recommended amount of fruit and vegetables [30].…”
Section: Homa-irmentioning
confidence: 99%
“…Despite the well-recognised impact diet quality can have on diabetes-related health outcomes, our systematic review has shown that, people with T2D have low-quality diets because they do not meet fruit, vegetable, wholegrain or low-fat dairy food group recommendations and meet or exceed the red meat and meat alternatives food group recommendations 10 . This suggests strategies to support healthy eating for people with T2D are still required.…”
Section: Introductionmentioning
confidence: 83%
“…This suggests strategies to support healthy eating for people with T2D are still required. However, this review was limited by the fact that the included studies were all of cross-sectional design 10 . Prospective designs are required to investigate what dietary changes people make immediately after T2D diagnosis and the demographic and health characteristics related to these changes 11 .…”
Section: Introductionmentioning
confidence: 99%
“… 17 A recent systematic review analyzed 11 studies (after screening roughly 12 000) and found that those with diabetes do not meet recommendations for specific food groups. 5 They consumed, on average, 0.5–2.5 servings a day under the nationally recommended amounts of fruits, vegetables, dairy, and grains and more than a serving a day over the recommended amounts of meat. 5 …”
Section: Discussionmentioning
confidence: 99%
“… 5 They consumed, on average, 0.5–2.5 servings a day under the nationally recommended amounts of fruits, vegetables, dairy, and grains and more than a serving a day over the recommended amounts of meat. 5 …”
Section: Discussionmentioning
confidence: 99%